Glucocerebrosidase Mutations and Synucleinopathies. Potential Role of Sterylglucosides and Relevance of Studying Both GBA1 and GBA2 Genes - Franco, Rafael; Sánchez-Arias, Juan A.; Navarro, Gemma; Lanciego, José L. (Frontiers in Neuroanatomy, 2018)
Gaucher’s disease (GD) is the most prevalent lysosomal storage disorder. GD is caused by homozygous mutations of the GBA1 gene, which codes for beta-glucocerebrosidase (GCase). Although GD primarily affects peripheral tissues, the presence of neurological symptoms has been reported in several GD subtypes. GBA1 mutations have recently deserved increased attention upon the demonstration that both homo- and heterozygous GBA1 mutations represent the most important genetic risk factor for the appearance of synucleinopathies like Parkinson’s disease (PD) and dementia with Lewy bodies (LBD). Although reduced GCase activity leads to alpha-synuclein aggregation, the mechanisms sustaining a role for GCase in alpha-synuclein homeostasis still remain largely unknown. Furthermore, the role to be played by impairment in the physiological function of endoplasmic reticulum, mitochondria and other subcellular membranous components is currently under investigation. Here we focus on the impact of GCase loss-of-function that impact of the levels of sterylglucosides, molecules that are known to trigger a PD-related synucleinopathy upon administration in rats. Moreover, the concurrence of another gene also coding for an enzyme with GCase activity (GBA2 gene) should also be taken into consideration, bearing in mind that in addition to a hydrolytic function, both GCases also share transglycosylation as a second catalytic activity. Accordingly, sterylglycoside levels should also be considered to further assess their impact on the neurodegenerative process. In this regard -and besides GBA1 genotyping- we suggest that screening for GBA2 mutations should be considered, together with analytical measurements of cholesterol glycosides in body fluids, as biomarkers for both PD risk and disease progression.